Techniques, Safety, and Therapeutic Effect of Percutaneous Cryoablation for Patients with Hepatocellular Carcinoma - Wang, MD, Chunping; Yang, MD, Yongping (North American Journal of Medicine and Science, 2016)
Hepatocellular carcinoma (HCC) is the third most common cause of cancer-related deaths worldwide and the second most common cause in China. The rate of resection of HCC is limited to 20-30%. Therefore, various local ablative therapies such as radiofrequency ablation (RFA), percutaneous cryoablation (PC), microwave, and percutaneous ethanol injection therapy, which play an important role in the treatment of HCC, have been developed [1]. Recently, PC, a local ablative therapy, has been developed with several advantages (such as ability to produce larger and more precise zones of ablation) over RFA and other thermal ablation treatments. This review mainly focuses on the indications, techniques, patient management, safety, and efficacy associated with PC for patients with HCC. [N A J Med Sci. 2016;9(2):66-70. DOI: 10.7156/najms.2016.0902066]